Old age work and income security in middle income countries: Comparing the cases - Carla Henry; Matías Goldman (International Labour Organization (ILO), 2021)
This paper considers the rapid demographic ageing trend experienced in many middle-income countries and examines how the dimensions of these demographic shifts can be combined with other dimensions related to employment, retirement and social protection in order to classify countries according to their level of preparedness to secure adequate income for their rapidly ageing population. This paper differs from other such studies as it deliberately incorporates employment measures and distributional aspects alongside economic and social protection measures in calculating a preparedness and vulnerability index. Patterns of work and income security up to and during old age were incorporated into the index using data from 35 middle-income and upper-middle-income countries, all of which will face ageing populations over the next 10 to 30 years. The index presented in this paper differs from other indices as it incorporates current employment dimensions relevant to the delivery of old-age income security in the future. Drawing from a wide array of country-specific indicators, this study seeks to identify configurations of descriptive variables that can approximate underlying relative differences between countries in terms of economic and social preparedness, distributional vulnerability and gender inequality. The results of the factor analysis suggest that, for social preparedness, the standard of living and strength of social protection in a country are two important underlying factors. For distributional vulnerability, the relative prevalence of low-quality employment and of poverty combined with inequality are the two dominant underlying factors which can be used to distinguish between countries. Finally, for gender inequality, the employment gender gap is the main factor, comprising gender differences in labour force participation and in youth preparedness for employment, both of which significantly influence life-long earnings and retirement income.
Keywords: 330; older workers; social protection; social security; ageing population; older persons